A stalactite record of four relative sea-level highstands during the Middle Pleistocene Transition. (1st October 2017) - Stocchi, Paolo; Antonioli, Fabrizio; Montagna, Paolo; Pepe, Fabrizio; Lo Presti, Valeria; Caruso, Antonio; Corradino, Marta; Dardanelli, Gino; Renda, Pietro; Frank, Norbert; Douville, Eric; Thil, François; et al.
Abstract: Ice-sheet and sea-level fluctuations during the Early and Middle Pleistocene are as yet poorly understood. A stalactite from a karst cave in North West Sicily (Italy) provides the first evidence of four marine inundations that correspond to relative sea-level highstands at the time of the Middle Pleistocene Transition. The speleothem is located ∼97 m above mean sea level as result of Quaternary uplift. Its section reveals three marine hiatuses and a coral overgrowth that fixes the age of final marine ingression at 1.124 ± 0.2, thus making this speleothem the oldest stalactite with marine hiatuses ever studied to date. Scleractinian coral species witness light-limited conditions and water depth of 20–50 m. Integrating the coral-constrained depth with the geologically constrained uplift rate and an ensemble of RSL scenarios, we find that the age of the last marine ingression most likely coincides with Marine Isotope Stage 35 on the basis of a probabilistic assessment. Our findings are consistent with a significant Antarctic ice-sheet retreat. Highlights: A stalactite with coral encrustations is found within a cave at ∼97 m above msl in NW Sicily. The cave experienced long-term tectonic uplift. The stalactite section reveals four marine inundations across the Middle Pleistocene Transition. A significant Antarctic Ice Sheet retreat caused the last marine ingression and a local RSL rise of 20–30 above present msl.